Learning from the experience of maternity healthcare workers in Malawi: a qualitative study leading to ten low-cost recommendations to improve working lives and quality of care - Abi Merriel; Julia Hussein; Address Malata; Arri Coomarasamy; Michael Larkin (BMC, 2018)
Abstract Background In Malawi there are too few maternity healthcare workers to enable delivery of high quality care to women. These staff are often overworked and have low job satisfaction. Skilled maternity healthcare workers are essential to improve outcomes for mothers and babies. This study focuses on understanding the working life experience of maternity staff at district hospitals in Malawi with the aim of developing relevant low-cost solutions to improve working life. Methods A qualitative study using semi-structured interviews was undertaken in three district hospitals around Malawi's Capital city. Thirty-one staff formed a convenience sample, purposively selected to cover each cadre. Interviews were recorded, transcribed and then analysed using Interpretative Phenomenological Analysis complemented by Template Analysis to elicit the experience of maternity staff. Results Staff describe a system where respect, praise and support is lacking. Many want to develop their skills, however, there are barriers to advancement. Despite this, staff are motivated; they are passionate, committed professionals who endeavor to treat patients well, despite having few resources. Their 'superdiverse' background and experience helps them build resilience and strive to provide 'total care'. Conclusions Improving working lives can improve the care women receive. However, this requires appropriate health policy and investment of resources. There are some inter-relational aspects that can be improved with little cost, which form the ten recommendations of this paper. These improvements in working life center around individual staff (respecting each other, appreciating each other, being available when needed, performing systematic clinical assessments and communicating clearly), leadership (supportive supervision and leading by example) and the system (transparent training selection, training being need driven, clinical skills being considered in rotation of staff). To improve working lives in this way will require commitment to change throughout the health system. Thus, it could help address preventable maternal and newborn deaths.